Correlation of the electrophysiological profiles and sodium channel transcripts of individual rat dorsal root ganglia neurons - Thériault, Olivier; Chahine, Mohamed (Frontiers in Cellular Neuroscience, 2014)
Voltage gated sodium channels (Na+ channels) play an important role in nociceptive transmission. They are intimately tied to the genesis and transmission of neuronal firing. Five different isoforms (Nav1.3, Nav1.6, Nav1.7, Nav1.8, and Nav1.9) have been linked to nociceptive responses. A change in the biophysical properties of these channels or in their expression levels occurs in different pathological pain states. However, the precise involvement of the isoforms in the genesis and transmission of nociceptive responses is unknown. The aim of the present study was to investigate the synergy between the different populations Na+ channels that give individual neurons a unique electrophysical profile. We used the patch-clamp technique in the whole-cell configuration to record Na+ currents and action potentials from acutely dissociated small diameter DRG neurons (<30 µM) from adult rats. We also performed single cell qPCR on the same neurons. Our results revealed that there is a strong correlation between Na+ currents and mRNA transcripts in individual neurons. A cluster analysis showed that subgroups formed by Na+ channel transcripts by mRNA quantification have different biophysical properties. In addition, the firing frequency of the neurons was not affected by the relative populations of Na+ channel. The synergy between populations of Na+ channel in individual small diameter DRG neurons gives each neuron a unique electrophysiological profile. The Na+ channel remodeling that occurs in different pathological pain states may be responsible for the sensitization of the neurons.